2020
DOI: 10.1111/obr.13050
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, waist circumference and body fat are positively correlated with hair cortisol in children: A systematic review and meta‐analysis

Abstract: Summary The current body of research lacks a meta‐analysis of the relationship between hair cortisol concentration (HCC) and anthropometry in children. Therefore, this systematic review and meta‐analysis was conducted to examine this relationship and explore possible moderators between HCC and body mass index (BMI/BMI z‐score). Eleven databases were searched: CINAHL, Cochrane, Embase, PsycEXTRA, Psychology and Behavioral Sciences, PsycINFO, PubMed, Scopus, Social Sciences Full Text, Sociological Abstracts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
4
14
2
Order By: Relevance
“…Our findings contrast with meta‐analyses that have suggested that links between HFI and body fat tend to be most common among women and among populations living in higher‐income or more‐industrialized nations (4,5) and uncommon or in the opposite direction among children and populations living in lower‐income or less‐industrialized nations (5,23). Our results also contrast with findings from meta‐analyses that have demonstrated overall positive, albeit not universal, associations between HCC and adiposity among adults (35) and children (36), as we found no such associations among adults and negative associations among children. This study raises questions regarding the kinds of buffers and compensatory mechanisms (both physiological and behavioral) that explain the null or positive associations between some measures of HFI and adiposity and null or negative associations between HCC and adiposity.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings contrast with meta‐analyses that have suggested that links between HFI and body fat tend to be most common among women and among populations living in higher‐income or more‐industrialized nations (4,5) and uncommon or in the opposite direction among children and populations living in lower‐income or less‐industrialized nations (5,23). Our results also contrast with findings from meta‐analyses that have demonstrated overall positive, albeit not universal, associations between HCC and adiposity among adults (35) and children (36), as we found no such associations among adults and negative associations among children. This study raises questions regarding the kinds of buffers and compensatory mechanisms (both physiological and behavioral) that explain the null or positive associations between some measures of HFI and adiposity and null or negative associations between HCC and adiposity.…”
Section: Discussioncontrasting
confidence: 99%
“…When insufficient data were reported for meta‐analysis, corresponding authors were contacted twice in a 2‐week time frame. In case of nonresponse, data were extracted from previous meta‐analyses where possible 9,12 …”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that variation in HairF levels on study level could be related, among other factors, to differences in mean BMI of the study populations 9 . Gray et al and Ling et al also reported that BMI and BMI standard deviation score (SDS), that is, BMI z ‐scores adjusted for age and sex that are most often used in pediatric studies, 10 were important determinants of HairF levels in children 11,12 . However, in the last years, many new large‐scale studies in various age categories have been published that have investigated the relation between HairGC and anthropometric features.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, in the elderly, other factors such as inflammation or body fat distribution may be involved and confound the results. Recently, another meta‐analysis reported the associations between HCC and adiposity in children (71). Despite the existence of some inconsistencies, when studies are pooled together in a meta‐analysis, the link between HCC and obesity seems to be conserved across the life‐span, possibly indicating the existence of a connection between trait measurement of HPA axis activity rather than state measurement.…”
Section: Discussionmentioning
confidence: 99%